Structure Study in Phonology and Physics - الألي, الرافع; Charef, Nadia; Charef, Samira (Wisdom Journal For Studies & Research, 2021)
Our current era is characterized by the openness and coordination of sciences, after the specialization trend was dominated for decades in scientific, human and social research, so we don't talk anymore about the limited isolated specializations, and each specialization became linked to a network of knowledge and to the sciences surrounding it, whether in constructing concepts or in constructing the subject of science itself, believing in the cognitive benefit that can be achieved by the openness of science and its interaction with other sciences, and drawing limits for the sciences has become one of the difficult matters, in fact, a single specialization appears in many faces as a result of the different specializations that attract it, accordingly, we chose a side of these specializations, and the idea of the study was entitled: “Interdisciplinarity in Phonetics and Physics,” it aims to emphasize the relationship between phonology and physics, by subjecting the sounds of the language to modern electronic programs and audio and digital devices in order to highlight its significance in the linguistic context, as well as its audio clarity.